1999
DOI: 10.1038/sj.leu.2401313
|View full text |Cite
|
Sign up to set email alerts
|

TEL-AML1 fusion transcript designates a favorable outcome with an intensified protocol in childhood acute lymphoblastic leukemia

Abstract: CORRESPONDENCE TEL-AML1 fusion transcript designates a favorable outcome with an intensified protocol in childhood acute lymphoblastic leukemia TO THE EDITORDespite the striking success that has been achieved in the treatment of acute lymphoblastic leukemia (ALL), 20-25% of children eventually relapse. 1 Several well-accepted clinical and biological features are of prognostic value: age between 1 and 10 years, leukocyte count of less than 50 000/ l, and hyperdiploid content (DNA index у1.16Ͻ1.60) all predictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Shurtleff et al (1995) suggested that this ALL subgroup was characterized by an excellent prognosis, although the 5‐year event‐free survival (EFS) was not significantly better than for the t(12;21)‐negative cases. Similar data indicating a favourable outcome for this patient cohort have since come from several retrospective studies (McLean et al , 1996; Borkhardt et al , 1997; Avigad et al , 1999; Maloney et al , 1999; Jamil et al , 2000; Uckun et al , 2001) as well as from a recent prospective study in which the survival rate was significantly better for BCP ALLs with ETV6/RUNX1 than for those without this fusion (Loh et al , 2006). However, many investigators have not observed any statistically significant survival differences between t(12;21)‐positive and ‐negative ALLs (Lanza et al , 1997; Takahashi et al , 1998; Kempski et al , 1999; Codrington et al , 2000; Hann et al , 2001; Hubeek et al , 2001; Pajor et al , 2001).…”
supporting
confidence: 77%
“…Shurtleff et al (1995) suggested that this ALL subgroup was characterized by an excellent prognosis, although the 5‐year event‐free survival (EFS) was not significantly better than for the t(12;21)‐negative cases. Similar data indicating a favourable outcome for this patient cohort have since come from several retrospective studies (McLean et al , 1996; Borkhardt et al , 1997; Avigad et al , 1999; Maloney et al , 1999; Jamil et al , 2000; Uckun et al , 2001) as well as from a recent prospective study in which the survival rate was significantly better for BCP ALLs with ETV6/RUNX1 than for those without this fusion (Loh et al , 2006). However, many investigators have not observed any statistically significant survival differences between t(12;21)‐positive and ‐negative ALLs (Lanza et al , 1997; Takahashi et al , 1998; Kempski et al , 1999; Codrington et al , 2000; Hann et al , 2001; Hubeek et al , 2001; Pajor et al , 2001).…”
supporting
confidence: 77%
“…With the sensitivity level of 10 −4 in the nested RT-PCR employed in this study, rapid clearance of the TEL/ AML1 fusion gene on completion of the induction therapy in 50% of the patients suggested that TEL/ AML1+ leukemic clones were highly sensitive to chemotherapy. Many reports suggest excellent prognosis for patients with the TEL/AML1 rearrangement and propose that the TEL/AML1 fusion gene is an independent favorable prognostic factor in childhood ALL [14,28,[33][34][35]. However, some recent conflicting reports challenged the prognostic impact of the TEL/AML1 rearrangement [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…ETV6-RUNX1 fusion protein is expressed in 25% of childhood B-lineage ALL cases and is associated with favorable prognosis following conventional therapeutic strategies [23][24][25][26][27][28]. However, some patients relapse at a late stage during therapy or after therapy, while they could also achieve sustained second remission.…”
Section: Introductionmentioning
confidence: 99%